Moodelling of processes and formal methods - Riesco, Daniel Eduardo (2002)
We proposed her a technique, which can be employed within the methodology know as process reengineering. This technique was applied in a government environment, which included an Information System and Geographical Information System, developed with financial support from The World Bank. One model used in process reengineering is the process model diagram. Ir allows finding the tasks, to be completed in each area of the organization. To understand the domain is crucial to be able to specify each one of these tasks. We show here how to use modeling of processes to find the tasks and to formalize their description using RAISE formal method. In this way, using a model of process as input, an engineer employs a systematic technique to create –as a starting point- the mail functions (tasks) of the domain using the RAISE formal method.